Effect of Projet-Based Learning on the Creative Personality, Teamwork Competence and Self-Regulated Efficacy of Undergraduate Nursing Students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper deals with learner-centered teaching methods according to the demand for improvement in university education. Project-based learning methods improve students’ self- learning and creative problem-solving ability. In clinical practice, creative problem-solving ability and teamwork competence are important among nurses’ competencies. This purpose of study was to apply a project-based learning method to curriculum to see changes in creative personality, teamwork competence, and self-regulated efficacy. This study conducted from September to December 2019 with 34 participants. To achieve this purpose, 34 students taking a health program development and evaluation course were tested for their creative personality, teamwork competence, and self-regulation efficacy. The analysis results showed that it is effective in creative personality, teamwork competency, and self-regulation efficacy (p